Profile of periodontal disease associated by diabetes mellitus, hypertension, asthma in RSGMP Hasanuddin University year 2023-2024: Profil penyakit periodontal disertai diabetes melitus, hipertensi, asma di RSGMP Universitas Hasanuddin tahun 2023-2024 - Ramadhani, Atikah Dhiya; Djulianra, Dzaky Sabrina; Nur, Syeck Jabal; Gani, Asdar; Adam, Mardiana; Hasanuddin; Oktawati, Sri; Djais, Arni Irawaty; Supiaty (Makassar Dental Journal PDGI Makassar, 2025)
The purpose of this study was to determine the profile of periodontal disease in patients with diabetes mellitus, hypertension, and asthma at RSGMP Hasanuddin University in 2023-2024. The type of research used is quantitative research with descriptive re-search design with cross-sectional study design. The study was conducted on periodontal disease patients suffering from DM, hypertension, and asthma who came to RSGMP Unhas in 2023. The results of the study found 2048 patients with periodontal disease at RSGMP Unhas in 2023. Female gender was found to be more common, namely 1319 patients (54.78%) and male patients as many as 1089 (45.22%). The frequency distribution of periodontal disease accompanied by DM, male sex as many as 8 (5%) patients and female 8 (5%) patients, for the distribution of hypertension in female patients found as many as 17 people (47.22%) while in male patients found as many as 19 people (52.77%). Asthma patients, male gender as many as 1 patient (0.25%) and female 3 patients (0.75%). Conclusion The frequency distribution of periodontal disease accompanied by DM and hypertension most often found chronic periodontitis. And for asthma patients, periodontal diseases found were chronic periodontitis, gingival enlargement, irreversible pulpitis and apical abscess.